ANALYSIS OF GREEN MARKETING STRATEGY IN ATTRACTING MILLENNIAL CONSUMERS WHO CARE ABOUT THE ENVIRONMENT - Rahmayati Rahmayati; Yunarti Yunarti; Mutmainna Mutmainna (CV. Adiba Aisha Amira, 2025)
The increase in environmental awareness among millennial consumers encourages companies to adopt green marketing strategies as an approach that is not only ethical but also strategic. This research aims to analyze effective green marketing strategies in attracting millennial consumers who are concerned about sustainability. Using a systematic literature review method, data were obtained from national and international scientific journals, academic articles, and industry reports published within the last five to ten years. The results of thematic analysis and narrative synthesis indicate that product-led approaches, eco-labeling, and green branding are the most effective strategies. The response of millennial consumers is influenced by factors such as trust, price, brand credibility, and authentically communicated sustainability values. Green marketing strategies have also proven to contribute to the formation of a positive brand image, consumer loyalty, and the long-term reputation of the company. Thus, green marketing has great potential in building sustainable relationships between brands and millennial consumers.